Gastroschisis with malrotation, gut duplication and Meckel's diverticulum; a rare association - Ahmed Elrouby, MD; Ahmed Maher, MS (Journal of Pediatric Surgery Case Reports, 2021)
Gastroschisis is defined as a congenital anterior abdominal wall defect which is rarely associated with other congenital anomalies. Gastrointestinal anomalies are the most common associations including malrotation. Other gut anomalies like intestinal duplication and Meckel's diverticulum are very rare. Our report a rare case of gastroschisis who is associated with malrotation, intestinal duplication and Meckel's diverticulum.